THE ROLE OF STAKEHOLDERS IN ETHNO-CULTURAL TOURISM DEVELOPMENT PLANNING IN KADUNA STATE, NIGERIA - Ibrahim, Aliyu H.; Falola, J. A. (FUDMA JOURNAL OF SCIENCES, 2021)
The paper evaluates the anticipated benefits and the perceived host community support for ethno-cultural tourism resource development in Kaduna State, Nigeria. Multi-stage sampling technique was adopted for this study. Six local governmentsâ€™ areas were chosen purposively because they accommodate different ethnic and cultural diversity within the state, representing about 33% of the total number of 23 LGAs in the state and have an estimated population of 1,639,621. The selected LGAs are also heterogeneous in terms of ethnicity, culture and religion. Semi-structured interview were administered to 316 respondents selected in the study area. Survey data were obtained through focus group discussion (FGD) in each ethnic community. FGDâ€s were held with youths, elders and aged. The sampled communities are Ham, Fulani, Hausa, Kagoro, Adara and Gbagyi, field observations were also carried out for holistic resource inventory in the ethnic communities. Documentary data were obtained from desk review method; information on tourism resources available in each ethnic community. The study reveals that the anticipated benefits of ethno-cultural tourism expected by the host communities are basically in terms of infrastructural development (road, water, electricity and communication services) and essential amenities (accommodation, restaurant, Tourist Travel Services, banking and bureau de change). The study recommends that lack of financial capital is a great hindrance for local communities to invest in the tourism industry. A mechanism for financial assistance, including provision of soft loans, needs to be in place in order to encourage host communities to invest in the industry. In turn, this would